Recent progress of g-C3N4 applied in solar cells - Yang, Xiaojie; Zhao, Li; Wang, Shimin; Li, Jin; Chi, Bo (Journal of Materiomics, 2021)
Graphite carbon nitride (g-C3N4), a two-dimensional polymer semiconductor material, has good semiconductor properties, suitable electronic energy band structure, excellent physical and chemical stability. It is widely used in the field of energy and materials science such as photoelectric conversion. In this paper, the progress of g-C3N4 in dye sensitized solar cells (DSSC) and perovskite solar cells (PSC) was reviewed. As a new semiconductor material, g-C3N4 has the advantages of simple preparation, abundant amino and Lewis basic groups. Therefore, on the basis of excellent structure of g-C3N4, its electronic and optical properties are utilized to further expand its application in the field of photoelectric conversion. [Display omitted] •This review summarizes the application of g-C3N4 in solar cells.•The g-C3N4 application of dye sensitized solar cells and perovskite solar cells are introduced in detail.•The g-C3N4 improvement of solar cell are discussed.